Application of FAST in patient with ischemic stroke and risk for ineffective cerebral perfusion: A nursing case study - Nur Fitria Ulfa Chasanah; Jon Hafan Sutawardana; Rondhianto Rondhianto; Mustakim Mustakim (School of Health Sciences Al-Ma'arif, 2025)
Background: Stroke is a neurological disorder frequently associated with reduced cerebral perfusion and impaired consciousness. While conventional interventions are widely implemented, their effectiveness may be enhanced by evidence-based approaches such as Familiar Auditory Sensory Training (FAST), a non-pharmacological intervention that utilizes meaningful auditory stimuli to activate neural pathways and support consciousness recovery. Objective: This study aims to evaluate the effectiveness of FAST in addressing the nursing problem of risk for ineffective cerebral tissue perfusion in an ischemic stroke patient. Methods: A case study was conducted involving a 73-year-old male patient in a soporous state. FAST was administered over three consecutive days, three times daily, with each session lasting 10 minutes. Data were collected through direct observation and Glasgow Coma Scale (GCS) measurements before and after each session. Patient outcomes were evaluated using the Nursing Outcomes Classification (NOC), focusing on indicators including consciousness level, blood pressure, and agitation. Results: The patient’s level of consciousness improved from sopor (6) to somnolence (9). Improvements were also noted in blood pressure, heart rate, and respiratory rate, although an increase in restlessness was observed. FAST supported cerebral responsiveness and cognitive function recovery, contributing to the resolution of the nursing problem: risk for ineffective cerebral tissue perfusion. Conclusion: FAST can be utilized as a therapeutic nursing intervention to enhance hemodynamic stability in patients with decreased consciousness